Analysis of Criminal Policy Against the Spread of Pirated Films Online (Study in the Bandar Lampung Region) - Ayu Kartika Putri (LEGAL BRIEF, 2018)
The development of information and communication technology makes piracy in the field of Copyright as land to take advantage of it and make Indonesia as a haven for the plowing so that the holders of intellectual property rights are harmed many despite tight control on it. The problem in this thesis is How the policies used to combat the spread of plowing movie works online as well as What are the factors inhibiting the copyright protection efforts in the dissemination of plowing movies online by law enforcement and related parties. This study uses the approach of juridical normative and empirical. This type of data consists of primary and secondary data. Analysis of data using qualitative analysis. Based on the results of research and discussion it can be concluded that have three stages there are the first stage is formulation stage, then application stage and the last is execution stage. There are several things that factor inhibitors such as law enforcement is limited to the parties who served in the police and in court both judges and investigators as well as in terms of legal factors, cultural factors, factors means and facilities as well as the factor of public awareness of the low level of public knowledge about IPR.